Biomechanical report for the IAAF World Championships London 2017 4 x 100 m relay Women's - Pollitt, L.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
While the quickest teams during the heats secured the gold (United States, 41.84 s) and silver (Great Britain & N.I., 41.93 s) medals, the medal positions were ultimately determined by a scrappy handover and final transition. A lengthy handover (1.10 s) for Jamaica, accounting for almost half of the total time spend in transition (48.5%), resulted in the longest transition of the race (2.26 s), costing them their slender lead (0.06 s) coming into the transition. And while none of the medallists produced an efficient handover of the baton between the final two legs, it was the loss of momentum that proved costly for Jamaica; who were without Elaine Thompson. Had Jamaica produced the effectiveness displayed within the prior transitions (2.02 and 2.09 s), they likely would have maintained their lead to capture gold. The impact of Jamaica's extended final transition is also illustrated by the highest variance (5.9%) across teams during the final. While the United States and Great Britain & N.I. improved their consistency in comparison to their performances during the heats, the final transition resulted in the longest transition time for all teams, apart from Switzerland. Nevertheless, for Switzerland, greater consistency in the final did not return an improvement in the total cumulative transition time and thus narrowly missed out on setting another national record which was recorded during the heats (i.e., 42.50 s). In contrast, despite greater efficiency within each transition, Germany could not improve upon the impressive performance displayed in winning their heat. Germany also exhibited the highest consistency in handover duration (variance 9.6%). In contrast, the medallists could not reproduce the efficiency displayed in the heats. For Jamaica, the longer duration in transition 3 was associated with a longer handover duration. Moreover, a shorter handover did not necessarily ensure a shorter transition time. For example, although the United States recorded their quickest handover in transition 2 (0.190 s), the total transition time (2.105 s) was almost identical to that recorded for transition 1 (2.110 s) where the handover was almost three times as long (0.565 s). While this may indicate that handover duration is not the pivotal factor, the total cumulative handover time was lower for the non-medal winning teams which may suggest that a quick handover compromises running speed. Because of the high levels of consistency for the time spent in transition, this report aimed to consider other key performance factors involved within each transition. It may even provide an indication of the tactics employed by each team. An effective handover within a transition should ensure that maximum speed is maintained; and ultimately minimise any loss in time. An ineffective handover could, however, occur due to many factors. Therefore, in addition to the duration of the transition and the handover, the duration of the delivery (i.e., baton entry to start of handover), and receive (i.e., end of handover to baton exit) legs, as well as the time spent in transition of the receive leg before baton entry were considered. This provides useful information about the relative position each team completed the handover. It also enabled an analysis of where time was lost or gained on the winning team within each transition. With respect to the duration of the delivery and receive legs within transitions, few trends can be observed. Some teams displayed a decrease in the delivery leg thus an increase in the duration of the receive leg over consecutive transitions (i.e. GBR, TTO), whereas some displayed the reverse trend to this (i.e., BRA, NED). The remaining teams recorded the shortest delivery, thus longest receive leg duration, within transition 2. This information ultimately highlights where the baton handover occurred and could in part reflect the tactics that were employed by each team. It could also reflect the strengths of individual athletes. For example, in general, the United States and Jamaica preferred to begin and complete the handover early in the transition, a tactic which may be employed to enhance the exit speed from the transition. Nevertheless, the exit speed would however be compromised by an inefficient handover. This can be seen in transition 3 for both the United States and Jamaica. However, having individual 100m gold medallist in Torie Bowie, meant that the challenge from Great Britain & N.I. was nullified. To highlight the ineffective final handover for the USA, Bowie can be observed to turn and look back to check the position of the delivery leg (i.e., Akinosun). Another contributing factor could have been the change in line-up for the last leg in the final (i.e. Bowie for Washington). In contrast, Jamaica changed both their line-up and their running order to record a faster time than in the heats, whereas Great Britain & N.I. made no changes and were less effective than during the heats. Another factor which may have prevented Great Britain & N.I. taking advantage within transition 3 was the notably earlier handover position compared to the heats (i.e., 6.7% vs. 25.2%), as well as the time spent by the receive leg in transition before baton entry (i.e., 3.7% vs. 10.1%). Despite similar transition durations, this earlier handover may have resulted in greater braking from the delivery leg and thus a reduction in the starting speed of the receive leg. Although Great Britain & N.I. were quicker than the United States in the second half of the transition (?0.135 s) the impact of this may be illustrated by a longer time spent in the first half of the transition (0.160 s) even though the United States could not complete an efficient handover. In summary, the outcome of the women's final may have been different but for ineffective performances in the final transition. Likewise, an effective performance by the United States may have resulted in another world leading performance. The team of Aaliyah Brown, Allyson Felix, Morolake Akinosun and Bowie were significantly faster than all other teams (e.g. 0.330 s vs. Great Britain & N.I.) between transitions which highlights the importance of raw speed. As they were only marginally slower than other teams within transitions (i.e., max 0.095 s), they were clearly very effective within the transition and with the handover. (Attention! registration on the IAAF site is required for downloading)